Enhancing antioxidant defense systems and regulating fatty acid unsaturation: Salicylic acid-mediated alleviation of low-temperature stress in Pitaya seedlings - Xian Luo; Ya Luo; Andong Xu; Xiaomei Kong; Xiaoli Wang; Qunxian Deng; Huifen Zhang; Lijin Lin; Yongxia Jia (BMC Plant Biology)
Abstract Low temperature (LT) restricts the growth and development of pitaya, therefore mitigating these detrimental LT-induced effects is of significant agricultural and economic importance in subtropical regions. This study investigated the effects of exogenous salicylic acid (SA, 2 mM) on the antioxidant system, fatty acid components, degree of unsaturation, and fatty acid desaturases (FADs) gene expression in pitaya seedlings (‘Taiwan No. 6’) under LT stress. LT stress increased reactive oxygen species (ROS), malondialdehyde (MDA), and relative electrical conductivity (REC), causing visible chilling injury (CI = 0.63). Crucially, LT also elevated saturated fatty acids (C12:0, C16:0, C18:0, C22:0) and decreased unsaturated fatty acids (C16:1, C18:2). This reduced the unsaturation ratio (UFA/SFA) and double bond index (DBI), compromising membrane stability and increasing permeability. However, SA application effectively mitigated these effects. SA improved peroxidase (POD) and catalase (CAT) activities, scavenging ROS and preventing oxidative damage. Crucially, SA upregulated the expression of genes encoding stearoyl-ACP desaturase (SAD) and fatty acid desaturases (FAD) enzymes, such as HuSAD2, HuFAD2, HuFAD4, HuFAD6. Consequently, SA increased unsaturated fatty acid proportions (C16:1, C18:2), UFA/SFA, and DBI. This restored membrane stability and integrity, lowered MDA, REC, and markedly reduced CI (to 0.38). This study demonstrates, for the first time in pitaya, that exogenous SA enhances cold resistance by activating antioxidant systems and regulating HuSADs and HuFADs gene expression to maintain membrane fatty acid unsaturation.